Who Wears the Chain? - Lavery-Yisraeli, Yonah (The review of rabbinic Judaism, 2023)
The recent debate regarding the eligibility of converts to Judaism (gerim) to sit on a beṯ din – a judicial panel – is unexpected. In the 19th century, when rabbis first begin to answer questions about whether or not gerim may serve on panels for the conversion of other potential gerim, the tone is consistently one of surprise: the answer was an obvious yes. In later reflections, however, the tone shifts, with increasing demands for definitive proof that no prohibition exists. But such a proof has been hard to articulate based on the classical sources. This article contends that the eligibility of a ger to sit a beṯ din was at one point obvious because such acceptance mirrors a central characteristic of classical Jewish judicial culture, which rests on welcoming strangeness and, hence, human strangers. Truth, this is, was understood to arrive through a gap rent in the familiarity that ordinarily rests between members of a community.